ANALISIS BEBAN KERJA GUNA EFISIENSI DI HOTEL GRAND BALISANI SUITES KEROBOKAN KUTA - Ni Putu Widiastuti; JB. Widiyanto Setiawan (STIE BIITM, 2020)
ABSTRACTAnalysis The Workload in improving the Efficiency at Hotel Grand Balisani Suites KerobokanKuta. This research aimed to analyze The Workload in improving the Efficiency at HotelGrand Balisani Suites Kerobokan Kuta. The sample of this research is 33 respondents athousekeeping department, Hotel Grand Balisani Suites Kerobokan Kuta. The Data sourcesused in this research are primary and secondary data. Data collection method in thisresearch using interview method and observation. The analytical technique used isdescriptive quantitative. Results of analysis known that the use of productive work time basedhousekeeping given workload is 6 hours or 360 minutes per day. Ideal number ofrequirements in Housekeeping Department for Public area is 12 people, its means that thereis over employees at public area unit is 5 people, at room unit is 12 people, laundry unit is 4,its means for this units are already optimal for ideal number of employee. The efficiency athousekeeping department Hotel Grand Balisani Suites Kerobokan Kuta is Rp.210.000.000/year or Rp. 17.500.000/month.